Experimental study on the floor responses of a base-isolated frame structure via shaking table tests. (15th February 2022) - Jung, Jae-Wook; Kim, Min Kyu; Kim, Jung Han
Highlights: Response characteristics of a base-isolated structure were experimentally investigated. Shaking table tests were performed to analyze dynamic properties and earthquake response of base-isolated structure. The seismic isolation structure was dominantly influenced by the low-frequency components of the input earthquake. Due to the nonlinear hysteretic behavior of the seismic isolator, the behavior of the base-isolated structure also exhibited complex behavior. Abstract: Seismic isolation represents one of the innovative means to improve the seismic safety of nuclear power plants (NPPs) against strong earthquakes. Many difficulties remain, though, in applying seismic isolation systems to real NPP structures due to the variability of the material properties of seismic isolators and the nonlinear behavior characteristics of the base isolation system in spite of the elastic behavior of the superstructure. Specifically, there is a limit to estimate the dynamic properties of base isolation systems for numerical analysis. The in-structure response of a base isolated-structure, which is related to equipment safety installed on the floors, is more sensitive than the base shear of the superstructure to the nonlinear properties of the isolation system. In this study, the complex behavioral characteristics of a base-isolated elastic frame structure are experimentally investigated through shaking table tests. Variation in response according to the frequency contents of the input earthquake is investigated, and the earthquake responses of the base-isolated structure for each frequency range are analyzed. In addition, the nonlinear increment of the in-structure response spectra to input ground motion intensity is evaluated, along with the nonlinear behavior of the seismic isolators. The experimental results obtained in this study can help identify various behavioral characteristics of base-isolated structures, with the nonlinear properties examined here acting as important references for evaluating the seismic safety of base-isolated NPPs.